2021
DOI: 10.1093/plcell/koaa045
|View full text |Cite
|
Sign up to set email alerts
|

The glycosyltransferase UGT76B1 modulatesN-hydroxy-pipecolic acid homeostasis and plant immunity

Abstract: The tradeoff between growth and defense is a critical aspect of plant immunity. Therefore, the plant immune response needs to be tightly regulated. Salicylic acid (SA) is an important plant hormone regulating defense against biotrophic pathogens. Recently, N-hydroxy-pipecolic acid (NHP) was identified as another regulator for plant innate immunity and systemic acquired resistance (SAR). Although the biosynthetic pathway leading to NHP formation is already been identified, how NHP is further metabolized is uncl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 49 publications
1
84
0
1
Order By: Relevance
“…Further studies revealed that its signaling function was more complex with glycosylated derivatives implicated [ 89 ]. Independent targeted and untargeted metabolomics strategies [ 90 , 91 ] identified UGT76B1 as a glucosyltransferase that modifies bioactive NHP, by catalyzing the formation of 1-O-glucosyl-pipecolic acid. Interestingly, UGT76B1 can also multitask, using SA and dihydroxybenzoic acid derivatives as substrates [ 92 ], implicating a pivotal role in modulating immune signaling.…”
Section: Metabolomics Research In Molecular Plant Pathology—challenges and Complexitymentioning
confidence: 99%
“…Further studies revealed that its signaling function was more complex with glycosylated derivatives implicated [ 89 ]. Independent targeted and untargeted metabolomics strategies [ 90 , 91 ] identified UGT76B1 as a glucosyltransferase that modifies bioactive NHP, by catalyzing the formation of 1-O-glucosyl-pipecolic acid. Interestingly, UGT76B1 can also multitask, using SA and dihydroxybenzoic acid derivatives as substrates [ 92 ], implicating a pivotal role in modulating immune signaling.…”
Section: Metabolomics Research In Molecular Plant Pathology—challenges and Complexitymentioning
confidence: 99%
“…Overexpression of AtUGT76D1 leads to high SA accumulation, upregulation of defense genes and the autoactive HR phenotype, while the immune responses were compromised when AtUGT76D1 is knocked out implying that AtUGT76D1 is a positive regulator in plant innate immunity (Huang et al, 2018). Interestingly, AtUGT76B1, a close homolog which had 38.8% similarity of amino acid with AtUGT76D1, was recently found to use N-hydroxy-pipecolic acid (NHP) as substrate and act in systemic-acquired resistance (Bauer et al, 2021;Holmes et al, 2021;Mohnike et al, 2021). Loss-of-function mts of AtUGT76B1 confer a dwarf phenotype and constitutive defense response, with high NHP and SA accumulation and enhanced disease resistance to PstDC3000 (Bauer et al, 2021;Mohnike et al, 2021).…”
Section: Sa and Glycosylation Of Sa Derivatives May Play A Role In Defense Responsementioning
confidence: 99%
“…Interestingly, AtUGT76B1, a close homolog which had 38.8% similarity of amino acid with AtUGT76D1, was recently found to use N-hydroxy-pipecolic acid (NHP) as substrate and act in systemic-acquired resistance (Bauer et al, 2021;Holmes et al, 2021;Mohnike et al, 2021). Loss-of-function mts of AtUGT76B1 confer a dwarf phenotype and constitutive defense response, with high NHP and SA accumulation and enhanced disease resistance to PstDC3000 (Bauer et al, 2021;Mohnike et al, 2021). The 2,5-DHBA glucosides were also accumulated in tomato and cucumber after infection with the pathogen, citrus exocortis viroid (CEVd) and prunus necrotic ringspot virus (PNRSV) (isolate NCM1), respectively (Fayos et al, 2006).…”
Section: Sa and Glycosylation Of Sa Derivatives May Play A Role In Defense Responsementioning
confidence: 99%
“…Rekhter et al (2019) showed that conversion of pipecolic acid into NHP is not dependent on SA but establishment of SAR may require positive interplay of NHP and SA (Hartmann and Zeier, 2019). Pipecolic acid and NHP move systemically in plants (Návarová et al, 2012; Y.,-C., Mohnike et al, 2021) but their presence in xylem sap has not been reported yet. Early findings of Návarová et al (2012) suggested NHP rather than pipecolic acid, as the bioactive component inducing SAR.…”
Section: Xylem Saps Shows Distinct Responses To Nitrate and Ammonium Nutritionmentioning
confidence: 99%
“…An LC-MS approach was used for phytohormone analysis, as described by Herrfurth and Feussner (2020) and Mohnike et al (2021). For phytohormones extraction, 200 µL unprocessed xylem sap and 750 µL phytohormone solution (10 ng D4 JA-Leu (kindly provided by Otto Miersch, Halle/Saale, Germany), 10 ng D6-ABA, 10 ng D4-SA (both from C/D/N Isotopes Inc., Pointe-Claire, Canada), 50 ng D9-Pip (Merck KGaA) and 50 ng 13 C6-SAG (kindly provided by Prof. Petr Karlovsky, Goettingen, Germany) in 750 µL methanol) were mixed.…”
Section: Phytohormone Analyses In Xylem Sapmentioning
confidence: 99%